Ergonomic conditions of the work of the team of nursing in an unit of cardiology - Marziale, Maria Helena Palucci (1998)
Aiming at finding out the ergonomics conditions of the nursing personnel in a hospital admission unit, the authors utilized as a methodological presuposition the search for a global experienced work situation through the analysis of some elements as: the man (nursing worker); the work activity (prescribed duty, real activities and work position) and the environment (temperature, noise and illumination). The authors selected the Cardiology admission unit for the site of their research. The results verified that the nursing workers the mentioned unit face problems related to salaries, work installations, relationship, work organization, levels of formation and the activities executed. The authors suggested some recommendations.